Group Guidance with Gestalt Support Based on Ukhuwah Islamiyah in Madrasah Aliyah, UIN Laboratory, North Sumatra, Medan - Siahaan, Dina Nadira Amelia; Zunidar, Zunidar (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2020)
Ukhuwah Islamiyah is an equivalent term for good social interaction between individuals in Islam. The concept of ukhuwah or brotherhood can be realized through guidance and counseling efforts. In the "world" this guidance and counseling effort is known as group guidance services. This paper aims to examine group guidance in improving ukhuwah Islamiyah through a gestalt approach with discussion techniques at Madrasah Aliyah Laboratory (MAL) UIN North Sumatra Medan. This research is focused on how the group guidance service efforts with discussion techniques in improving ukhuwah Islamiyah at MAL UIN North Sumatra Medan and what factors support and hinder the process. For this reason, a qualitative approach with a descriptive-analytical method is appropriate to uncover empirical truths of research. The results of this study indicate that group counseling services with discussion techniques can improve student ukhuwah Islamiyah at MAL UIN North Sumatra Medan. This is indicated by (1) good interpersonal communication between students; (2) students' familiarity in finding solutions to shared problems; (3) tolerance of differences in argumentation; and (4) empathy for the situation felt by peers.